1976
DOI: 10.1113/jphysiol.1976.sp011217
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the contractility of mammalian myocardium at low rates of stimulation.

Abstract: 1. Measurements have been made of tension development in papillary muscles isolated from the right ventricles of young cats. In some cases membrane potentials have also been recorded, using micro electrodes. 2. Regular contractions at a stimulation rate of 20 min(-1) (the 'standard' rate used in this study) had the following characteristics (30 degrees C): peak tension developed, about 43mN mm(-2); time to peak tension and time to 80% repolarization of the cell membrane, about 400 ms. 3. The corresponding figu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
108
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(125 citation statements)
references
References 21 publications
17
108
0
Order By: Relevance
“…1). Such a late maximum has been reported for heart muscle of the rat (Scriabine, 1959), and of the cat at high Ca2+ concentration or a high frequency of stimulation (Allen, Jewell and Wood, 1976).…”
Section: Psupporting
confidence: 61%
“…1). Such a late maximum has been reported for heart muscle of the rat (Scriabine, 1959), and of the cat at high Ca2+ concentration or a high frequency of stimulation (Allen, Jewell and Wood, 1976).…”
Section: Psupporting
confidence: 61%
“…We previously reported that the peculiar force-frequency relationship in rat atria was differently affected by aand P-adrenoceptor stimulation, especially at a higher range of stimulation rates (Hattori & Kanno, 1984). Complexly intertwined processes, sometimes acting in opposite directions, determine the actual tension developed at a constant stimulation rate (Chapman, 1979), and changing the stimulation interval may unmask a fundamental step ofcellular Ca2" dynamics (Allen et al, 1976;Edman & J6hannsson, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In general, prolonged RI resulted in smaller T 1 /T ss . This phenomenon, which is known as "rest decay", reflects spontaneous leakage of Ca 2+ from SR [1,7,16]. "Rest decay" was seen in both non-diabetic and diabetic muscles (Fig.…”
Section: Figmentioning
confidence: 97%
“…Such a contraction is called a postrest contraction (PRC) or rested-state contraction [20]. However, the first contraction is larger than that of the steady-state contraction when stimulated after a short rest interval [1,3,5,11,23,24]. This potentiation of PRC is highly dependent on augmented Ca 2+ release from the sarcoplasmic reticulum (SR) [1,6,29].…”
Section: Introductionmentioning
confidence: 99%